Investigating formulaic expressions in an informal YouTube broadcast interview video - Tsani, Talitha Anindya; Galuh Kirana Dwi Areni (ELT Forum: Journal of English Language Teaching, 2025)
This study investigates the use of formulaic expressions in spontaneous informal communication found in a YouTube video titled 50 Cents: 50 Minutes You Can’t Afford to Ignore in a podcast interview format. The focus of this study is to analyze the types, frequencies, and pragmatic functions and meanings of the use of formulaic expressions in conversational contexts based on Celce-Murcia’s Communicative Competence theory (2007) and discourse analysis approach. The identified expressions are then categorized based on four types such as routines, collocations, idioms, and lexical frames. The findings show that collocations are the most frequent expressions in the video followed by lexical frames, routines, and idioms. These results indicate that formulaic expressions, especially collocations and lexical frames, play an important role in maintaining the flow of interaction so that it runs smoothly, naturally, and effectively in the context of informal interaction. This study also highlights how the implications of using formulaic expressions to convey ideas or messages in an easy-to-understand, effective, clear, and interesting way can strengthen the emotional bond between the speaker and the interlocutor or audience. The findings are also in line with several previous studies that have examined the dominance of the use of formulaic expressions in different contexts. This study contributes to a deeper understanding of the use of verbal language through digital platforms, provides insight into the use of formulaic expressions in real-life spontaneous interactions, and can be used as a reference for future linguistic research with a focus on digital communication or discourse.